Mission of the Church Under Pressure—An Orthodox Perspective. Issue 2 (June 2015) - Dumitraşcu, Nicu
Abstract Mission always has focused on the constituent elements of the church, which are an intrinsic part of the church's very existence. Mission therefore is defined directly in relation to evangelism. This study aims to present briefly two of the today's missionary challenges from an Orthodox perspective. The first is how to preserve cultural and religious identity in a polymorphic society in all aspects, and how to eliminate the risk of confusing it with an ideology. The second refers to the missionary dimension of monasticism and the efficiency of the professional practice of the spiritual competences.